No evidence of direct contribution of adult plant stages to climate adaptation in snapdragon plants. Issue 1 (2nd January 2022) - Gibert, Anaïs; Marin, Sara; Latutrie, Mathieu; Marrot, Pascal; Mouginot, Pierick; Archambeau, Juliette; Baillet, Vincent; Coriat, Emilie; Perron Kyritsos, Théodore; Pujol, Benoit
ABSTRACT: Signatures of local adaptation have been found at all life stages in plants. Yet, the contribution of later plant stages is rarely disentangled from the influence of early-life stages. Here, we investigate the direct contribution of adult plant stages to climate adaptation in two subspecies of snapdragon plants ( Antirrhinum majus ), while growth conditions have been homogenized at early-life stages. We compared genetic variation in fitness proxies ( i.e . flowering, number of flowers and survival) and phenotypic traits in adult plants of eight populations of A. m. pseudomajus and seven populations of A. m. striatum, in two common garden experiments at high and low elevations. We found no evidence of adaptation to elevation in adult plants in both subspecies. Populations of low-elevation habitats outperformed populations of high-elevation habitats in all gardens. The effects of phenotypic traits on fitness components were similar at high and low elevation, suggesting no divergent selection along elevation. Different traits had an effect on fitness proxies in A. m. striatum and A. m. pseudomajus, suggesting that different mechanisms are at play in these two subspecies. Our findings suggest that there is no direct contribution of adult plant stages to climate adaptation in snapdragon plants and that adaptive processes potentially differ at the scale of A. majus subspecies.